Impact of the injector design on the combustion noise of gasoline partially premixed combustion in a 2-stroke engine. (5th June 2017) - Broatch, A.; Margot, X.; Novella, R.; Gomez-Soriano, J.
Highlights: The impact of the injector design on combustion noise in gasoline PPC has been evaluated. The maximum pressure time-derivative mainly determines the combustion noise level. Resonance phenomenon can contribute as a relevant source of combustion noise. Controlling fuel stratification by injector design is critical to control combustion noise. Three combustion-related parameters have been identified to control the resonance level. Abstract: In this paper, a numerical Computational Fluid Dynamics (CFD) study is carried out with the purpose of understanding how the injector design may impact on the in-cylinder processes, which cause noise emission. This study is based on a combination of the gasoline partially premixed combustion concept with a new high speed direct injection 2-stroke engine, which emerges as a promising solution able to comply with nitrous oxides and particulate matter emissions standards, while ensuring combustion control and stability. The original engine configuration is varied by modifying the included spray angle and the number of injector nozzles in order to evaluate other design solutions for mitigating combustion noise. Results show that the maximum pressure time-derivative achieved during the combustion is the most influential parameter on the acoustic response of the in-cylinder noise source. However, they also evidence that for some operation conditions the resonance phenomena can enhance their contribution, thus playing a relevant role in the engine noise level. Further analysis allowed to identify three combustion-related parameters, which characterise this phenomenon and allow identifying key paths to minimize its levels.